A Comparison of Adaptive Functioning Between Children With Duplication 7 Syndrome and Williams-Beuren Syndrome: A Pilot Investigation - Alfieri, Paolo; Scibelli, Francesco; Montanaro, Federica Alice Maria; Caciolo, Cristina; Bergonzini, Paola; Dentici, Maria Lisa; Vicari, Stefano (Frontiers in Psychiatry, 2022)
Interstitial deletions of 7q11.23 cause the well-known Williams–Beuren Syndrome (WBS), while duplication of the same region leads to duplication 7 syndrome (Dup7). Children with WBS share a distinct neurobehavioral phenotype including mild to severe intellectual disability, severely impaired visual spatial abilities, relatively preserved verbal expressive skills, anxiety problems, enhanced social motivation (i.e., hypersociable behaviors) and socio-communicative problems. Children with Dup7 syndrome exhibit some “inverted” features when compared to those of individuals with WBS, such as reduced social motivation and impairment of expressive language. Direct comparison of WBS and Dup7 represents a unique opportunity for the neurobehavioral characterization of the 7q11.23 section. However, most of the available data come from qualitative analysis between different studies. To the best of our knowledge, there are no studies directly comparing features of two matched samples of individuals with WBS and Dup7 syndromes. In this pilot study, we compare the adaptive functioning – measured with the Vineland Adaptive Behavior Scales, Second Edition – of two relatively small samples of children with molecularly confirmed diagnosis of WBS and Dup7 matched for IQ and chronological age, with a particular attention to socialization domain and expressive subdomain. Contrary to our assumption, we have not found any significant difference on socialization domain and expressive subdomains. This pilot investigation suggests that, when matched for chronological age and cognitive level, children with WBS and Dup7 share more similarities than expected. The inverted features that emerge in clinical settings on expressive language and social motivation seem not to differently interfere with the daily abilities to communicate and socialize with meaningful others during daily lives. Differences highlighted by previous undirected comparisons could be due to general and non-specific factors such as cognitive level, which is more severely impaired in individuals with WBS than Dup7. Implications for assessment and treatment are discussed.